Simulations on the survivability of Tidal Dwarf Galaxies. Issue Volume 10:Issue S309(2014) (9th February 2015) - Ploeckinger, Sylvia; Recchi, Simone; Hensler, Gerhard; Kroupa, Pavel
Abstract: We present detailed numerical simulations of the evolution of Tidal Dwarf Galaxies (TDGs) after they kinematically decouple from the rest of the tidal arm to investigate their survivability. Both the short-term (500 Myr) response of TDGs to the stellar feedback of different underlying stellar populations as well as the long-term evolution that is dominated by a time dependent tidal field is examined. All simulated TDGs survive until the end of the simulation time of up to 3 Gyr, despite their lack of a stabilising dark matter component.